ASSESSING MOTOR REHABILITATION OF POST-STROKE PATIENTS USING THE MOTOR ASSESSMENT SCALE - Tuyết, Trần Thị Kim; Nghĩa, Phan Trọng; Trường, Nguyễn Văn Nhật; An, Trần Viễn (Journal of Health and Aging, 2025)
To evaluate the motor function recovery in post-stroke patients using the motor assessment scale (MAS). A prospective, interventional, cross-sectional descriptive study without a control group, with assessments before and after treatment. The study was conducted on 92 post-stroke patients who received examination and treatment at the Rehabilitation Department, Emergency Cardiology Intervention Department, Neurology Department, and Traditional Medicine Department of Thong Nhat Hospital from May 2023 to May 2024. Motor function recovery was evaluated using the MAS scale, which includes 8 main activities: lying, sitting, standing, walking, and upper limb and hand movements. Motor function improved significantly after treatment, with an average increase of 5.58 ± 0.83 points (p
Keywords: Motor Assessment Scale; rehabilitation; upper limb movement; stroke